2017
DOI: 10.5267/j.ijiec.2016.6.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of multi-response dynamic systems using multiple regression-based weighted signal-to-noise ratio

Abstract: A dynamic system differs from a static system in that it contains signal factor and the target value depends on the level of the signal factor set by the system operator. The aim of optimizing a multi-response dynamic system is to find a setting combination of input controllable factors that would result in optimum values of all response variables at all signal levels. The most commonly used performance metric for optimizing a multi-response dynamic system is the composite desirability function (CDF). The adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…The weighted MRDSN is considered as the objective function for the optimization problem. Gauri and Pal (2017) argue that a multiple regressionbased weighted S/N ratio (MRWSN) performance metric can overcome the limitations of the composite desirability function (CDF) for the multi-objective problems. The results have shown that the MRWSN method is superior to the CDF method in terms of optimization performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The weighted MRDSN is considered as the objective function for the optimization problem. Gauri and Pal (2017) argue that a multiple regressionbased weighted S/N ratio (MRWSN) performance metric can overcome the limitations of the composite desirability function (CDF) for the multi-objective problems. The results have shown that the MRWSN method is superior to the CDF method in terms of optimization performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Al-Refaie et al [13] integrated the desirability function and data envelopment analysis for solving dynamic systems with multi-responses. Gauri and Pal [14] proposed a multiple regression-based weighted signal-to-noise ratio (MRWSN) to optimize the multi-response dynamic systems.…”
Section: Introductionmentioning
confidence: 99%